1998
DOI: 10.1076/ceyr.17.7.730.5166
|View full text |Cite
|
Sign up to set email alerts
|

Different strains of Pseudomonas aeruginosa isolated from ocular infections or inflammation display distinct corneal pathologies in an animal model

Abstract: This study has identified that P. aeruginosa produces at least three different types of corneal pathology and that not all strains are able to infect mouse corneas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 0 publications
3
57
0
Order By: Relevance
“…3,46,47 Histologic assessment at days 3 and 7 was not possible, as the corneas perforated on enucleation. In addition to the clinical signs observed in the WT animals, PA keratitis in the KO mice presented with a grossly edematous and ectatic central cornea with ensuing descemetocele (keratocele) formation at the end stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,46,47 Histologic assessment at days 3 and 7 was not possible, as the corneas perforated on enucleation. In addition to the clinical signs observed in the WT animals, PA keratitis in the KO mice presented with a grossly edematous and ectatic central cornea with ensuing descemetocele (keratocele) formation at the end stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of timely and appropriate treatments, the infected cornea undergoes progressive degradation leading to perforation and therefore permanent vision loss. [3][4][5] The host immune response to PA corneal infection, which is critical in determining the outcome of the disease, consists primarily of an influx of neutrophils from the tear film and the limbal vasculature into the cornea. Previous studies suggest that both tissue-destructive bacterial proteases and stromal-degrading enzymes liberated by activated neutrophils and other stimulated inflammatory cells (e.g., macrophages) account for the corneal perforation observed in patients with severe PA keratitis.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Stock cultures of P. aeruginosa 6206 and 6294 stored in 30% glycerol at Ϫ70°C were inoculated into 10 ml of tryptone soy broth (Oxoid Ltd., Sydney, Australia). These strains of bacteria are well-characterized corneal iso-lates from cases of microbial keratitis (12) which lead to distinct corneal pathologies in a mouse model (7). Fleiszig et al (12) have demonstrated that strain 6206 is toxic to mammalian cells but that strain 6294 is an invasive strain and is engulfed by mammalian cells.…”
Section: Methodsmentioning
confidence: 99%
“…IL-10 gene knockout mice generated on a C57BL/6 background and C57BL/6 wild-type control mouse breeding stocks were obtained from Jackson Laboratories (Bar Harbor, Maine) and housed under specific-pathogen-free conditions at the Biological Resources Center, University of New South Wales, Sydney, Australia. Inbred 6-to 8-week-old mice were challenged with P. aeruginosa as previously described (7). The mice were examined for signs of systemic disease prior to the commencement of experiments, and only healthy mice were used for experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The cytotoxic strain 6206 of P. aeruginosa was used. Strain 6206 was isolated from a human corneal ulcer and classified as a cytotoxic strain on the basis of its interaction with corneal epithelial cells in vitro (8). Bacteria were grown in 10 ml of tryptone soy broth (Oxoid Ltd., Sydney, Australia) overnight at 37°C, harvested and washed three times in sterile phosphate-buffered saline (PBS), and resuspended in PBS prior to use.…”
Section: Methodsmentioning
confidence: 99%